Improving Students’ Reading Comprehension through Storytelling Frame - Kurniawan, Andri; Amalia, Puji Astuti; Indrawati, Indrawati (Poltanesa, 2024)
Reading is a basic skill that students must master and enjoy. Through reading, students can increase and improve their knowledge. However, reading is a challenging activity.  Based on the observation, the author found that Elementary students in SDN 012 had low abilities in reading activities. This low reading ability has an impact on limited student participation in reading activities.  Therefore, the author creates a story telling frame and stages of reading activities that can increase student participation in reading activities and improve students' reading skills. There were some stages done by the author. The first was designing a story telling frame, implementing reading activities with students, the second was using a story telling frame with students and teachers and the last was evaluating the story telling frame. The design of storytelling frame used square and round shape stainless in gold color. They were decorated with artificial flowers, dolls and cloth.  The story telling frame was designed based on the theme of the story, which is “where is bear?”. There were 20 students who joined the story telling activity using the story telling frame. The pre-test and post-test on students’ reading comprehension revealed that students have better understanding on reading the text by using story telling frame.